Illness identity in adults with congenital heart disease: Longitudinal trajectories and associations with patient‐reported outcomes and healthcare use. (9th July 2021) - Van Bulck, Liesbet; Goossens, Eva; Apers, Silke; Moons, Philip; Luyckx, Koen
Abstract: Aims: The aims of this study were to investigate the development of illness identity, the degree to which the disease is integrated into one's identity, by identifying trajectory classes in adults with congenital heart disease (CHD) and to describe these classes in terms of age, sex, disease complexity, patient‐reported outcomes (PROs) and healthcare use. Design: This three‐wave observational cohort study was carried from 2013 till 2015 and includes 276 adults (median age: 34 years; 54% men) with CHD. Methods: Illness identity entails four dimensions: engulfment, rejection, acceptance and enrichment. PROs included perceived health status, quality of life and psychological distress. Latent class growth analysis, analysis of variance, Poisson regression and negative binomial regression analyses were performed. Results: Illness identity was relatively stable over time. The identified classes were meaningfully different in terms of age, disease complexity, PROs and healthcare use. Patients who did not reject their disease, patients who were not overwhelmed or patients who accepted their disease over time reported better health status and quality of life and less psychological distress. Less hospitalizations and visits to the general practitioner and medical specialist were reported by patients who were not overwhelmed or patients who accepted their disease over time. Patients with low rejection and high enrichment scores over time reported more visits at the general practitioner. Conclusion: These findings indicate that illness identity should be taken into account when trying to understand and optimize PROs and healthcare use of adults with CHD. Impact: This study scrutinizes the development and clinical meaningfulness of illness identity measured over time for adults with CHD. Illness identity was found to be stable over time. Moreover, the illness identity trajectories differed in terms of PROs and healthcare use, showing that measuring and intervening upon illness identity could be a potential pathway to optimize PROs and healthcare use.